Productivity of Calliandra calothyrsus, Indigofera zollingeriana and Gliricidia sepium on acid soil in the greenhouse - Iwan Herdiawan; Endang Sutedi (Jurnal Ilmu Ternak dan Veteriner, 2015)
Acid soil which contains Al3+ and Mn2 is generally unfavorable for crop including the tree legumes. The minerals are toxic to the plants resulted minimalization of growth and crop production. Caliandra calothyrsus, Indigofera zollingeriana, and Gliricidia sepium were tree legumes those are generally used for forage.  The aim of this study was to compare their tolerancy to Al3+ and growth production on acid soil. The plants were grown in ultisol soil with 4.57 of pH collected from Palm Oil plantation, Sei-Putih, Medan. The experiment was carried out using completely randomized design (CRD) with kind of plants as the treatment and 12 times replication. The data were analyzed by ANOVA using the SPSS and excel program, followed by LSD test when the data was significantly difference. Variables measured were plant morphology, concentration of Al 3+ in the plant tissues, plant height, stem diameter, number of stem branches, root length, plant production, nutrient content, energy and in vitro digestibility. The highest Al 3+ contents in leaves, stem and root were significantly observed in those G. sepium, while the lowest contents was observed from those of  I. zollingeriana. G. sepium was the most dwarf plant and its stem diameter was comparable with the one of C. calothyrsus, but was lower than that of I. zollingeriana. The highest number of branches was significantly observed in I. zollingeriana, while the lowest one was at G. sepium. The root length of C. calothyrsus was comparable with that of I. zollingeriana, while G. sepium root was the shorthest one. Root nodulation was only formed at I. zollingeriana. The highest biomass production was observed at I. zollingeriana which also had highest protein content and the best digestibility.  Data from Al3 + concentration in tissues of leaves, stems and roots showed that I. zollingeriana was the most tolerant plant to acid soils. This tolerancy also affected higher plant growth, biomass production, nutrient concentration, and digestibility.